1992
DOI: 10.1042/bj2870567
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the monomer-dimer reaction of yeast hexokinase PI

Abstract: Kinetic studies of the glucose-dependent monomer-dimer reaction of yeast hexokinase PI at pH 8.0 in the presence of 0.1 M-KCl have been carried out using the fluorescence temperature-jump technique. A slow-relaxation effect was observed which was attributed from its dependence on enzyme concentration to the monomer-dimer reaction; the reciprocal relaxation times tau-1 varied from 3 s-1 at low concentrations of glucose to 42 s-1 at saturating concentrations. Rate constants for association (kass.) and dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…In the case of ScHxk1, the same crystal form was analyzed (PDB entry, 3B8A) (29), whereas a new crystal form was obtained for ScHxk2 (PDB entry, 1IG8) (30). Remarkably, in all of these structures the enzymes are present in the monomeric state, even though ScHxk1 and ScHxk2 are known to form dimers (31). In contrast, dimeric arrangements have been observed in crystal forms BI (32) and BII (33) of ScHxk2; however, these dimers are asymmetric and consist of two subunits related by screw axes of 156°(BI) and 180°(BII) rotation and 13.8 Å (BI) and 3.6 Å (BII) translation.…”
mentioning
confidence: 99%
“…In the case of ScHxk1, the same crystal form was analyzed (PDB entry, 3B8A) (29), whereas a new crystal form was obtained for ScHxk2 (PDB entry, 1IG8) (30). Remarkably, in all of these structures the enzymes are present in the monomeric state, even though ScHxk1 and ScHxk2 are known to form dimers (31). In contrast, dimeric arrangements have been observed in crystal forms BI (32) and BII (33) of ScHxk2; however, these dimers are asymmetric and consist of two subunits related by screw axes of 156°(BI) and 180°(BII) rotation and 13.8 Å (BI) and 3.6 Å (BII) translation.…”
mentioning
confidence: 99%
“…It has been suggested that hysteresis in yeast hexokinase activity could be due to isomerization or dissociation of the molecule [41]. The slow isomerizations observed here, like the slow association-dissociation reactions observed previously [34], would be able to generate hysteretic effects.…”
Section: Quantitative Analysismentioning
confidence: 55%
“…Under these conditions, three relaxation effects were observed which, as discussed above, cannot be attributed to the association-dissociation reaction of hexokinase; this reaction is known to intervene at much higher pH and ionic strength [34]. The present results are interpreted within the framework of the concerted MWC model which is conceptually more straightforward and involves fewer independent parameters than either the sequential model or the more general model of Eigen [27].…”
Section: Quantitative Analysismentioning
confidence: 89%
See 2 more Smart Citations